PERENCANAAN ARSITEKTUR ENTERPRISE SISTEM INFORMASI PADA KANTOR OTORITAS PELABUHAN PENYEBERANGAN (KOPP) DITJEN PERHUBUNGAN DARAT - Yasmi Afrizal (Foristek, 2013)
Network Planning and infrastructure development at Kantor Otoritas Pelabuhan Penyeberangan (KOPP) has not reach mature level and causing overlap for Information Technology (IT) investment, unclear goals and it become less optimal. Therefore transportation ministry has to design a blue print of network infrastructure to achieve IT Governance and E – Governance strategy. Scope of this research is to design information system enterprise architecture at land tansportation directorat of KOPP to develop infrastructure for head office. Enterprise Architecture Planning (EAP) is a methode used for designing its infrastructure that has ability to define architecture process to use information for businees supporting and provide plan to implement the architecture. EAP blue print used to build and it helped KOPP to solve problem in architecture information system planning especially for application infrastructure component, data infrastructure and network infrastructure.